Comparing the effects of eight week ball exercises in water and Pilates on some muscle performance indices and mental health of Women with MS - Asieh Sadat Mousavian (Mashhad University of Medical Sciences, 2018)
Introduction: Multiple Sclerosis (MS) is a chronic disease of the demyelination of central nervous system which is characterized in the nerve by the disruption in the transmission. Considering to the effects of different exercises to help in decreasing the disease' symptoms in MS patients, this study was performed with aim to compare the effects of ball exercises in water and Pilates on the speed and endurance of walking, balance, fatigue and quality of life in women with MS. Methods: This applied and semi-experimental study was performed on 31 MS women with EDSS£4 who were resident in Mashhad and had referred to MS institute of Mashhad in 2016. The subjects were placed in three groups of ball exercises, Pilates, and control. The participants exercised three times a week for 8 weeks. Speed test data (10m walk test), walking durability (2-minute test), and Equilibrium test (BBS) were measured by time-meter. Fatigue test (FFS) questionnaire was used to measure the fatigue of patients and also pulsometer was used to measure the intensity of Pilates training programs and ball exercises in water (from 40-70% of maximum heart rate). Data was analyzed by SPSS software (version 18) and multivariate analysis of variance analysis, dependent-t, and Tukey follow-up test. P< 0.05 was considered significant. Results: Speed of walking was significantly increased in the group of ball exercises in water (P<0.001), while this increase was not significant in Pilates group (P=0.132). Endurance of walking and balance were significantly increased in the groups of ball exercises in water (P= 0.008, P-0.001) and Pilates (P= 0.009, P=0.002). Fatigue was significantly decreased in the groups of ball exercised in water (P= 0.004) and Pilates (P= 0.019). Quality of life was significantly increased in the groups of ball exercised in water (P= 0.000) and Pilates (P= 0.001). However, there was no significant difference between the two groups in all the indices. The control group didn't show changes in any indices. Conclusion: In terms of the measured indices, no changes have been observed in control group (P≥0.05). The information can be helpful and useful in designing the exercise programs for he patients with MS. Conclusion: Ball exercises in water and Pilates exercises along with drug therapies can improve the balance indexes, fatigue, speed and endurance of walking and quality of life in patients with MS, and with a targeted increase in the intensity and volume of activity, physical capacity, and quality of life of patients will increase.